Measuring Investor Sentiment on the Zimbabwe Stock Exchange - Mazviona, Batsirai Winmore (Asian Journal of Economic Modelling, 2015)
Investor sentiment is belief about future cash flows and investment risks not justified by current relevant information. Additionally, investment decisions made without support from information. In classical finance theory, investor sentiment does not play any role in the cross-section of stock prices, realized returns, or expected returns. But inexplicable events such as the crash of October, 1987, The Great Crash of 1929, the Tonics Boom and Go-Go Years of the 1960s, the Nifty Fifty bubble of the 1970s have cast doubt on the standard finance model in which stock prices equal the rational expectations of unemotional investors. Behavioural finance attempts to explain these disparities using investor sentiment. The aims of the study are to document market measures of investor sentiment and to demonstrate whether investor sentiment exerts an influence on the Zimbabwe Stock Exchange. Daily return and trading volume data of 66 stocks, excluding delisted and suspended stocks, for the period from 19 February 2009 to 31 December 2012 were considered. A high-low volume sentiment indicator variable is introduced to distinguish when the market has higher or lower sentiment. An ordinary linear regression was used to show the evidence of the effect of investor sentiment indicator on stock returns. The researcher found that approximately 40% of the market moved contrary to the market sentiment indicator. The remaining 60% co-moved with the sentiment indicator, with the level of effect differing in magnitude, indicating that the sentiment indicator had a positive effect on the indicator. However, these results though are not statistically robust using the binomial test as only five out of the sixty-six stocks (approximately 7%) were significant at a 5% interval. This is less than the number of significant results expected under the null hypothesis. Hence, the null hypothesis cannot conclusively be accepted or rejected, and the effect of the sentiment indicator on returns could not be completely ruled out or established.